CONSTITUTION AND THE GOALS OF SUSTAINABLE DEVELOPMENT IN THE DEVELOPMENT STRATEGY OF NEW UZBEKISTAN - Khabibulla Akhmedov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article discusses issues related to modern perspectives on ensuring human dignity and its personal, political, social, economic, cultural, ecological, and development rights in the Constitution and the Development Strategy of New Uzbekistan. It also explores the solutions to these issues in the context of sustainable development goals.